2023
DOI: 10.3390/microorganisms11122898
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Acute Liver Failure among Patients in Egypt Coinfected with Hepatitis A and Hepatitis E Viruses

Mohamed A. El-Mokhtar,
Amal A. Elkhawaga,
Mona Sedky Hussein Ahmed
et al.

Abstract: Hepatitis A virus (HAV) and Hepatitis E virus (HEV) are transmitted through the fecal–oral route. HAV outbreaks and one HEV outbreak have been reported in Egypt. However, the impact of HAV–HEV co-infection is not known. In this study, we assessed HEV markers in acute HAV-infected patients (n = 57) enrolled in Assiut University hospitals. We found that 36.8% of HAV-infected patients were also positive for HEV markers (anti-HEV IgM and HEV RNA), while 63.2% of the patients were HAV mono-infected. Demographic and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 67 publications
0
0
0
Order By: Relevance
“…Host factors Older age 163,171 Genetic factors 192,194 Viral factors HEV viral load 174,195 HEV genotype 163,164,195 Nucleotide mutation 172,208 Other factors Existence of chronic liver disease 229,232 Existence of metabolic disease 242,250 Coinfection of HAV 244 Abbreviations: HAV, hepatitis A virus; HEV, hepatitis E virus. women and 41-year-old men) contracted HEV infection through blood transfusion.…”
Section: Items Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Host factors Older age 163,171 Genetic factors 192,194 Viral factors HEV viral load 174,195 HEV genotype 163,164,195 Nucleotide mutation 172,208 Other factors Existence of chronic liver disease 229,232 Existence of metabolic disease 242,250 Coinfection of HAV 244 Abbreviations: HAV, hepatitis A virus; HEV, hepatitis E virus. women and 41-year-old men) contracted HEV infection through blood transfusion.…”
Section: Items Factorsmentioning
confidence: 99%
“…136 Recently, El-Mokhtar et al reported that the risk of ALF development was 8.5fold greater in patients coinfected with HAV and HEV than in those with monoinfection. 244 For HEV-ALF patients younger than 65 years, 21 liver transplantation should be considered a therapeutic option.…”
Section: Artificial Liver Support and Liver Transplantationmentioning
confidence: 99%
“…The liver function profile was comparable in the HAV-HEV coinfected patients and HAV mono-infected ones. However, the risk of acute liver failure was higher among the coinfected patients [37].…”
mentioning
confidence: 90%
“…However, the outcomes of this co-infection are not known. In this issue, EL-Mokhtar and colleagues reported that 36.8% of HAV-infected patients were HAV-HEVcoinfected ones [37]. The liver function profile was comparable in the HAV-HEV coinfected patients and HAV mono-infected ones.…”
mentioning
confidence: 94%